The Green function for the Neumann boundary value problem at the semiinfinite cylinder and the flat infinite baffle - Rdzanek, Wojciech; Rdzanek, Witold; Różycka, Anna (Archives of Acoustics, 2007)
This paper presents the Green function for the Neumann boundary value problem at the rigid semiinfinite cylinder and the flat rigid infinite baffle. The function has been expressed as the combination of the Hankel functions of the first and second kinds, and their derivatives – all n-th order. The acoustic pressure has been presented in the two cases: the time harmonic vibrations of a sector cylinder piston located on the semiinfinite cylinder, and the annular sector piston located on the flat baffle in the vicinity of the semiinfinite cylinder.